2015
DOI: 10.1111/asj.12475
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters for carcass defects of Japanese Black cattle in Kagoshima

Abstract: Cattle exhibit a range of carcass defects, including blood splash (BLS), intramuscular edema (INE), muscle steatosis (MUS), bruising (BR), trim loss (TRL) and others (OTH). These defects lower the carcass value and can result in significant economic loss to producers. We estimated the incidence, relationship with inbreeding coefficients and genetic parameters of carcass defects in Japanese Black cattle using 561 619 carcass records from Kagoshima, Japan during April 1988 through March 2011. The defect incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Atagi et al [ 25 ] detected detrimental effects of inbreeding in semen production traits. Nishi et al [ 26 ] observed a positive linear relationship between the defect incidence and inbreeding coefficients in muscle steatosis, bruising and trim loss, which all lower carcass value. However, few studies have investigated inbreeding depression using a genome-based inbreeding coefficient in Japanese Black cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Atagi et al [ 25 ] detected detrimental effects of inbreeding in semen production traits. Nishi et al [ 26 ] observed a positive linear relationship between the defect incidence and inbreeding coefficients in muscle steatosis, bruising and trim loss, which all lower carcass value. However, few studies have investigated inbreeding depression using a genome-based inbreeding coefficient in Japanese Black cattle.…”
Section: Introductionmentioning
confidence: 99%